Synthesis and characterisation of multi-walled carbon nanotubes on supported catalysts via catalytic chemical vapour deposition - Tee, Jia Chee (2006)
The main hindrance to employ carbon nanotubes (CNTs) commercially is the inability to control the growth of the nanotubes and to grow bulk amounts of carbon nanotubes. However, recently the Chemical Vapour Deposition (CVD) has been modified by applying various supported metals catalysts in the production of CNTs. Therefore, in this research we focus on the effects of supported catalysts in the synthesis of CNTs via Catalytic Chemical Vapour Deposition (CCVD) method. The CCVD method was used to synthesize high quality CNTs in high yield and economical cost with controlling of the CNTs characteristics and morphologies. A practical and high performance CCVD system has been designed and built. The fixed bed flow reactor in the CCVD system is specifically fabricated to carry out the pyrolysis of hydrocarbon to produce CNTs. The supported catalysts of cobalt (Co), iron (Fe) and mixture of these metals (Co/Fe) were prepared by using the alumina (Al2O3), molecular sieves (MS) and anodic aluminium oxide (AAO) template as supports. All supported catalysts were prepared by impregnation method. The asprepared supported catalysts were subjected to calcination at 450 Â°C. The catalysts were characterised using X-Ray Diffraction (XRD) technique. Acetylene (C2H2) was selected as the carbon precursor and the reaction was performed at 700 Â°C for 30 minutes. The yields of the reaction collected as black depositions on the catalysts. The characterisations of the yield were carried out using Scanning Electron Microscopy (SEM), Field-Emission Scanning Electron Microscopy (FE-SEM) and Transmission Electron Microscopy (TEM) as well as Energy Dispersive X-Ray Analysis (EDAX) techniques. Catalysts prepared were active in the production of CNTs. The most active catalysts were identified as Al-Co/Fe(3.0)Cal, AAO-Co/Fe(1.0)Cal and MS-Co/Fe(3.0)Cal as they generated high carbon contents of 72.00, 64.03 and 48.50 wt.% respectively. The as-grown CNTs over various catalysts showed high degree of graphitisation, purity and density with configurations of bundles, arrays and coils. The CNTs yields were classified as multi-walled carbon nanotubes (MWNTs). The best MWNT consists of 11 layers of turbostratic graphene wall with inner diameter of 3.57 nm and outer diameter of 11.43 nm as well as distance between layers of 0.33 nm. The CNTs grown over Al2O3 supported catalysts followed the tip growth mechanism whereas the CNTs grown over MS supported catalysts followed the base growth mechanism.